Identification and characterization of burkholderia pseudomallei K96243 serine and metallopeptidase - Azizan, Muhammad Talhah; Muhamad Bunnori, Noraslinda (2014)
Burkholderia pseudomallei K96243, the causative agent of melioidosis, is reported to produce various extracellular products, including proteases. The role of these proteases in the melioidosis, however, remains obscure. Previous findings have hinted at the inherent pathogenicity of the protease during B. pseudomallei K96243 infection. The annotated sequences by Wellcome Trust Sanger for the two families of metallopeptidases and serine peptidase are not full annotated.We chose to annotate the two major families peptidases, i.e. serine peptidases and metallopeptidases present in B. pseudomallei K96243. A total of 3065 non-redundant query sequences of characterized and predicted proteases were obtained and predicted proteases were obtained by using text searched and from a few databases (NCBI, MEROPS, BRENDA and UniProtKB). The redundant sequences will be omitted by using ARTEMIS tools. The BLASTP searched against B. pseudomallei K96243 genome and conserved domains/motifs were identified by searching InterPro database. The multiple sequence alignments and active sites are annotated by using ClustalX with known sequences from other organisms and the consequences were deduced by the BOXSHADE. There was only hydrolases classes (EC3) have been distinguished from a total eighty identified peptidases and comprised two type of compound/group involved which are EC3.5 (carbon-nitrogen bond) and EC3.4 (peptide bond). Only a peptidase from S45 family has predicted belongs to EC3.5 and the rest of 79 peptidases are hydrolases acting on peptide bond. There are seven groups specified based on the nature of reaction: EC3.4.11 (aminopeptidases), EC3.4.13 (dipeptidases), EC3.4.14 (dipeptidyl and tripeptidyl-peptidases), EC3.4.16 (serine-type carboxypeptidase), EC3.4.17 (metallo-type carboxypeptidases), EC3.4.21 (serine endopeptidases) and EC3.4.24 (metalloproteases) and each group comprised 30.8%, 3.8%, 2.6%, 12.7%, 1.3%, 27% and 20.5% respectively. Although EC3.4.11 has the highest percentage of peptidases but the group consists both serine and metallopeptidase unlike EC3.4.21 and EC3.4.24 which only have either serine or metallopeptidases.In this study, we have characterized 48 serine peptidases and 32 metallopeptidases based on their functional domains and active sites by making comparisons with known peptidase functions. The collection of 80 peptidases has been characterized based on EC group. The group of the peptide bond (EC3.4) accumulated about 98% of the total peptidase that has annotated. The classification for both serine and metallopeptidases to the peptidase family facilitate identifying the potential peptidases which contribute as virulence factors.